1993
DOI: 10.1159/000462399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Different Immunoassays and PCR for the Detection of Hepatitis C Virus Infection in Pregnant Women in Taiwan

Abstract: To compare different hepatitis C virus (HCV) immunoassays and HCV-RNA in pregnant women, we investigated two independent groups: 1,687 cases without screening for serum alanine aminotransferase (ALT) (group A) and 333 cases with elevated ALT (>45 IU/l) (group B), after screening 21,459 pregnant women. In group A, 11 (0.65%) and 21 (1.24%) were anti-HCV- positive by first- and second-generation tests, respectively, while in group B 8 (2.40%) and 19 (5.71%) were positive, respectively. The results revealed by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…We found among 2046 pregnant women a total of 42 (2.1%) viremic for GBV-C/HGV, a prevalence higher than that of HCV infection in the same population on Taiwan [19]. Furthermore, 52% (95% confidence interval, 32.4% -71.6%) of the viremic mothers transmitted GBV-C/HGV to their offsprings.…”
Section: Discussionmentioning
confidence: 79%
“…We found among 2046 pregnant women a total of 42 (2.1%) viremic for GBV-C/HGV, a prevalence higher than that of HCV infection in the same population on Taiwan [19]. Furthermore, 52% (95% confidence interval, 32.4% -71.6%) of the viremic mothers transmitted GBV-C/HGV to their offsprings.…”
Section: Discussionmentioning
confidence: 79%
“…4 In fact, 16 patients in our study had groupspecific antibodies but did not have serum HCV RNA, suggesting a past infection of HCV or an extremely low level of viremia that escaped detection by the present PCR. 4 Of interest, we found that patients with group 1 antibodies had a higher rate of viremia than those with group 2 antibodies (92% vs 62%, P < 0.005), and this gave support to previous studies showing that patients with genotype lb HCV have a greater amount of virus than those with genotype 2a. 40"41 Thus, the serotyping assay is obviously a practical alternative to current PCR genotyping methods and remains the only possible test in those positive for anti-HCV but negative for HCV RNA.…”
Section: Discussionmentioning
confidence: 64%
“…Since the development of first-generation sérologie assays (2), detection of anti-HCV has become the standard test for the diagnosis of HCV infection (3,9), and the presence of anti-HCV usually indicates infectivity (6,8,23). Accordingly, such tests have a major impact on screening of blood donors, which leads to a reduction in the incidence of posttransfusion non-A, non-B hepatitis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that second-generation anti-HCV assays perform much better than first-generation assays in the detection of HCV infection because of the incorporation of a highly conserved core peptide of the virus (3,(5)(6)(7)(8). Thus second-generation anti-HCV tests are now widely used for clinical diagnosis and blood donor screening (9).…”
Section: Introductionmentioning
confidence: 99%